2000
DOI: 10.1097/00003446-200006000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of Mismatch Negativity in School-Age Children

Abstract: Changes in the timing of the brain discriminative response, MMN, suggest systematic maturational changes in auditory processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
112
3
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(144 citation statements)
references
References 29 publications
26
112
3
3
Order By: Relevance
“…All these four ERP components were robustly observed after 6 months of age. These morphological changes are consistent with previous findings [2,14]. The amplitudes of N 250 and P 350 components gradually increased between 3 and 9 months.…”
Section: Morphological Changes Of Erp Componentssupporting
confidence: 92%
See 2 more Smart Citations
“…All these four ERP components were robustly observed after 6 months of age. These morphological changes are consistent with previous findings [2,14]. The amplitudes of N 250 and P 350 components gradually increased between 3 and 9 months.…”
Section: Morphological Changes Of Erp Componentssupporting
confidence: 92%
“…It appears that the most obvious decreases in MMN latency occurred within the first year. This result is parallel to previous studies [14]. Ejiri et al [29] also observed a progressive decrease in MMN latency in subjects within 7 years of age.…”
Section: Morphological Changes Of Mismatch Responsessupporting
confidence: 91%
See 1 more Smart Citation
“…In MMN studies with children (and adults), the stimuli are usually presented while the subject is engaged in some other activity, such as reading a book or watching a video with the sound turned down or off. The latency of the MMN in children is shorter than in infants, generally peaking between 150 to 300 ms following stimulus onset (81).…”
Section: Selective Allocation Of Attention In Children 3321 Autommentioning
confidence: 92%
“…Temporal principal components (PCs) accounting for a cumulative variance of 99% were included in the rotation (Kayser & Tenke, 2003). The PCs occurring at the latencies (approximately 100-200 ms) typically reported in the literature for MMN in school-aged children (e.g., Shafer, Morr, Kreuzer, & Kurtzberg, 2000) and showing comparable topographic distribution between the grand averaged CSD maps and PCA factor score maps were selected for further statistical analysis.…”
Section: Statistical Analyses 261 Group and Stimulus Comparisonsmentioning
confidence: 99%